2018
DOI: 10.1161/hypertensionaha.117.10787
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Supplementation With a Mitochondrial Antioxidant (MitoQ) Improves Vascular Function in Healthy Older Adults

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT02597023.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
257
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 322 publications
(281 citation statements)
references
References 40 publications
10
257
0
Order By: Relevance
“…Adequate concentrations of the cofactor BH 4 and the substrate tyrosine are essential for optimal activity of tyrosine hydroxylase, the rate-limiting enzyme required for NA synthesis (Kaufman, 1978;Moens & Kass, 2007). Increased oxidative stress is evident in primary ageing and contributes to age-associated cutaneous microvascular dysfunction (Rossman et al, 2018;Seals, Jablonski, & Donato, 2011). Tetrahydrobiopterin and tyrosine are susceptible to oxidation by reactive oxygen species (Li, Knowlton, Woodward, & Habecker, 2003) and are consequently reduced in aged skin (Lang, Holowatz, & Kenney, 2010).…”
Section: Ageingmentioning
confidence: 99%
“…Adequate concentrations of the cofactor BH 4 and the substrate tyrosine are essential for optimal activity of tyrosine hydroxylase, the rate-limiting enzyme required for NA synthesis (Kaufman, 1978;Moens & Kass, 2007). Increased oxidative stress is evident in primary ageing and contributes to age-associated cutaneous microvascular dysfunction (Rossman et al, 2018;Seals, Jablonski, & Donato, 2011). Tetrahydrobiopterin and tyrosine are susceptible to oxidation by reactive oxygen species (Li, Knowlton, Woodward, & Habecker, 2003) and are consequently reduced in aged skin (Lang, Holowatz, & Kenney, 2010).…”
Section: Ageingmentioning
confidence: 99%
“…The clinical trial reconfirmed the safety and tolerability of MitoQ. [49] The 20 mg/d dose of MitoQ was well tolerated, and no treatmentrelated serious adverse events occurred. Even after 160 mg of acute administration, only a few mild adverse reactions occurred.…”
Section: Clinical Research Of Tpp-based Antioxidantsmentioning
confidence: 62%
“…In 2018, a successful clinical trial that demonstrated the effects of MitoQ to improve vascular function in healthy older adults. The clinical trial reconfirmed the safety and tolerability of MitoQ . The 20 mg/d dose of MitoQ was well tolerated, and no treatment‐related serious adverse events occurred.…”
Section: Pharmacokinetics and Clinical Research Of Tpp‐based Antioxidmentioning
confidence: 64%
“…Mitochondrial targeted antioxidants have been shown to improve both large artery stiffness and EDD in old mice and older adults: however, in contrast to the results with TEMPOL described above, these improvements are largely independent of alterations in circulating and aortic cytokine production (Gioscia‐Ryan et al., , ; Rossman et al., ; Zinovkin et al., ). Mitochondrial targeted antioxidants decrease aortic ICAM in old mice (Zinovkin et al., ), and in rat endothelial cells scavenging of mitochondrial ROS attenuates NFκB activity and inflammatory cytokine production (Ungvari et al., ).…”
Section: Interventions To Ameliorate Age‐related Inflammation and Artmentioning
confidence: 97%